2003
DOI: 10.1016/s0094-114x(03)00098-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of compliant constant-force compression mechanisms

Abstract: A mathematical dynamic model is derived for compliant, constant-force compression-mechanisms, based on the pseudo-rigid-body model simplification of the device. The compliant constant-force compression mechanism (CFCM) is a slider mechanism incorporating large-deflection beams, which outputs near-constant-force across the range of its designed deflection. The equation of motion is successfully calibrated with empirical data from five separate mechanisms, comprising two basic configurations of CFCMs. The dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…As the connecting-rod link is a two-degreesof-freedom system, there is two relative velocities related to the crank and its coordinate . Therefore, the relative velocity of the connecting-rod considers the translational and rotational motions which is developed by using the cosines' law, denoting [23,24] …”
Section: Shock and Vibrationmentioning
confidence: 99%
“…As the connecting-rod link is a two-degreesof-freedom system, there is two relative velocities related to the crank and its coordinate . Therefore, the relative velocity of the connecting-rod considers the translational and rotational motions which is developed by using the cosines' law, denoting [23,24] …”
Section: Shock and Vibrationmentioning
confidence: 99%
“…For simplifying the analysis, the PRBM was also preferred. Mathematical Jacobian matrix for the constraint equations model of a compliant slider-crank mechanism was derived from a generalized PRBM using Lagrangian Dynamics [5]. Empirical results were also used to validate the theoretical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudo-rigid-body models have been developed for small-length flexural pivots (Howell and Midha, 1994), long flexible elements with force loads (Dado, 2001;Howell and Midha, 1995;Howell et al, 1996), flexible segments with combined force and moment loads (Saxena and Kramer, 1998;Su, 2009), and many others (Howell, 2001). These models have been successfully used in numerous applications, for example compliant linkages (Bandopadhya et al, 2009;Dado, 2005;Mattson et al, 2004), bistable mechanisms (Jensen et al, 1999;Masters and Howell, 2003;Sonmez and Tutum, 2008), and they have been demonstrated to be useful in dynamic applications (Boyle et al, 2003;Yu et al, 2005), Su (2009) developed an accurate pseudo-rigid-body model for combined loading conditions that employs combining pseudo-rigid links in a series to accurately model the motion. Currently, pseudo-rigid-body models assume that deflections remain in a single plane.…”
Section: Introductionmentioning
confidence: 99%